Preoperative ultrasound staging of the axilla make's peroperative examination of the sentinel node redundant in breast cancer: saving tissue, time and money. (November 2016) - Van Berckelaer, Christophe; Huizing, Manon; Van Goethem, Mireille; Vervaecke, Andrew; Papadimitriou, Konstantinos; Verslegers, Inge; Trinh, Bich X.; Van Dam, Peter; Altintas, Sevilay; Van den Wyngaert, Tim; Huyghe, Ivan; Siozopoulou, Vasiliki; et al.
Abstract: Objective: To evaluate the role of preoperative axillary staging with ultrasound (US) and fine needle aspiration cytology (FNAC). Can we avoid intraoperative sentinel lymph node (SLN) examination, with an acceptable revision rate by preoperative staging? Design: This study is based on the retrospective data of 336 patients that underwent US evaluation of the axilla as part of their staging. A FNAC biopsy was performed when abnormal lymph nodes were visualized. Patients with normal appearing nodes on US or a benign diagnostic biopsy had removal of the SLNs without intraoperative pathological examination. We calculated the sensitivity, specificity and accuracy of US/FNAC in predicting the necessity of an axillary lymphadenectomy. Subsequently we looked at the total cost and the operating time of 3 models. Model A is our study protocol. Model B is a theoretical protocol based on the findings of the Z0011 trial with only clinical preoperative staging and in Model C preoperative staging and intraoperative pathological examination were both theoretically done. sentinel node, staging, ultrasound, preoperative axillary staging, FNAC, axilla Results: The sensitivity, specificity and accuracy are respectively 0.75 (0.66–0.82), 1.00 (0.99–1.00) and 0.92 (0.88–0.94). Only 26 out of 317 (8.2%) patients that successfully underwent staging needed a revision. The total cost of Model A was 1.58% cheaper than Model C and resulted in a decrease in operation time by 9, 46%. The benefits compared with Model B were much smaller. Conclusion: Preoperative US/FNAC staging of the axillary lymph nodes can avoid intraoperative examination of the sentinel node with an acceptable revision rate. It saves tissue, reduces operating time and decreases healthcare costs in general.